THE EFFECT OF GIVING TOMATO JUICE ON REDUCING DYSMENORRHEA PAIN IN ADOLESCENT GIRLS AT SMPN 2 PARIAMAN - FIKRIANI, NURUL; ZANAH, MIFTAKHUL; ZAYANI, NOFRI (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
such as dizziness, fatigue, sweating, backache, headache, nausea, vomiting and diarrhea all occur before or during menstruation. Tomatoes contain lycopene, iron, potassium, calcium, vitamins A, B, D and G which function to relieve pain. The purpose of this study was to determine the effect of giving tomato juice on reducing dysmenorrhea pain in adolescent girls at SMPN 2 Pariaman. The research design used quasi-experimental. The study was conducted at SMPN 2 Pariaman on August 5-21, 2024. The study population of adolescent girls who experienced dysmenorrhea pain at SMPN 2 Pariaman amounted to 32 people. The research sample amounted to 15 people with accidental sampling data collection techniques. The research instrument was a numeric rating scale (NRS) observation sheet. The results of the study showed that there were 12 people (80%) out of 15 respondents was moderate before being given tomato juice and there were 14 respondents (93%) who experienced a decrease in mild pain levels after being given tomato juice. The results of the Wilxocon test obtained a p-value = 0.001 <α = 0.05. This means that the administration of tomato juice has an effect on reducing the intensity of pain in adolescent girls at SMPN 2 Pariaman. It can be concluded that the administration of tomato juice has an effect on reducing dysmenorrhea pain in adolescent girls at SMPN 2 Pariaman. The researcher's suggestion is that the results of the study can be used as an alternative choice of non-pharmacological therapy for adolescents who experience dysmenorrhea.